2010
DOI: 10.1111/j.1468-4446.2010.01312.x
|View full text |Cite
|
Sign up to set email alerts
|

Making a difference: ethical consumption and the everyday

Abstract: Our everyday shopping practices are increasingly marketed as opportunities to 'make a difference' via our ethical consumption choices. In response to a growing body of work detailing the ways in which specific alignments of 'ethics' and 'consumption' are mediated, we explore how 'ethical' opportunities such as the consumption of Fairtrade products are recognized, experienced and taken-up in the everyday. The 'everyday' is approached here via a specially commissioned Mass Observation directive, a volunteer pane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
93
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(101 citation statements)
references
References 37 publications
2
93
0
6
Order By: Relevance
“…A shopper who trusts certain labels, such as Fair Trade, can thus be helped by those labels, at least in terms of being relieved of the work of finding out the ethicality of products. However, not all shoppers believe the claims behind the labels, and some indeed see ethical branding as just cynical marketing [47]. Even with ecolabels, consumers still need to weigh up between products, and that decision-making must be repeated for each item in the shopping basket.…”
Section: Whose Choice: Consumer or Retailer?mentioning
confidence: 99%
See 3 more Smart Citations
“…A shopper who trusts certain labels, such as Fair Trade, can thus be helped by those labels, at least in terms of being relieved of the work of finding out the ethicality of products. However, not all shoppers believe the claims behind the labels, and some indeed see ethical branding as just cynical marketing [47]. Even with ecolabels, consumers still need to weigh up between products, and that decision-making must be repeated for each item in the shopping basket.…”
Section: Whose Choice: Consumer or Retailer?mentioning
confidence: 99%
“…Qualitative investigations into the ethics of shopping have revealed that rather than some consumers having ethical concerns and others not, in addition to the environmental and social conditions of production concerns more commonly thought of for ethical consumption, shopping always has ethical dimensions, such as caring for one's family, demonstrating thrift, even asserting national identity and political values [47,[49][50][51]. Two consumers making polar opposite choices about what to buy may both have an ethical framework underpinning their choice [51].…”
Section: Whose Choice: Consumer or Retailer?mentioning
confidence: 99%
See 2 more Smart Citations
“…in supporting either local food and/or Fairtrade products imported from other countries. Consumers may struggle when making ethical choices whilst considering to support British products or international food products (Adams and Raisborough, 2010). Vermeir and Verbeke (2006) also found that limited information and/or more complex or contradictory information may result in uncertainty among consumers on what products to purchase.…”
Section: Methodsmentioning
confidence: 99%